2022
DOI: 10.1091/mbc.e22-10-0468-t
|View full text |Cite
|
Sign up to set email alerts
|

Basal bodies bend in response to ciliary forces

Abstract: Motile cilia beat with an asymmetric waveform consisting of a power stroke that generates a propulsive force and a recovery stroke that returns the cilium back to the start. Cilia are anchored to the cell cortex by basal bodies (BBs) that are directly coupled to the ciliary doublet MTs. We find that, consistent with ciliary forces imposing on BBs, bending patterns in BB triplet MTs are responsive to ciliary beating. BB bending varies as environmental conditions change the ciliary waveform. Bending occurs where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
(127 reference statements)
0
8
0
Order By: Relevance
“…We speculate that centrioles with triplet microtubules and the proteins they anchor, including the inner scaffold, may be required for centriole function in organisms with motile cilia, perhaps to help stabilize the basal body against ciliary movement. Such activity has been described for Tetrahymena basal bodies, and mutating an inner scaffold protein, Poc1, results in abnormal bending within basal bodies (Junker et al, 2022). Further supporting this hypothesis, Drosophila spermatocytes, one of the few cells within this species with motile cilia, have basal bodies with triplet microtubules (González et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…We speculate that centrioles with triplet microtubules and the proteins they anchor, including the inner scaffold, may be required for centriole function in organisms with motile cilia, perhaps to help stabilize the basal body against ciliary movement. Such activity has been described for Tetrahymena basal bodies, and mutating an inner scaffold protein, Poc1, results in abnormal bending within basal bodies (Junker et al, 2022). Further supporting this hypothesis, Drosophila spermatocytes, one of the few cells within this species with motile cilia, have basal bodies with triplet microtubules (González et al, 1998).…”
Section: Discussionmentioning
confidence: 87%
“…We previously showed that BBs bend in response to the cilia beat stroke, suggesting that BBs balance rigidity with plasticity to ensure they do not disassemble (Junker et al, 2022). To understand how the BB architecture protects itself from ciliary forces, we used UExM-SIM to assess how BBs bend in response to ciliary beating.…”
Section: Resultsmentioning
confidence: 99%
“…Under high force conditions, WT BBs exhibit a gradual bend, whereas dramatic fracturing of the BB through the core region was observed in the absence of Poc1, suggesting poc1Δ BBs lack the structural integrity that can integrate the bending without destructive deformation (Fig. 6E; (Junker et al, 2022)). To determine whether BBs that show structural defects have intact core structures, we used UExM-SIM to visualize Poc16 in BBs in high force conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Centrioles are subcellular organelles with an evolutionarily conserved, barrel-shaped structure that are found at the base of cilia and flagella (reviewed in Azimzadeh, 2021; Winey and O’Toole, 2014). There, the centriole, also known as the basal body, acts as a shock absorber that resists the movement of axonemal microtubules relative to one other, although they may flex in response to ciliary forces (Junker et al, 2022). Yet, centrioles have evolved diverse structures in the sperm cells of many invertebrate and vertebrate animals, presumably due to divergent selective pressure produced by varying levels of sperm competition (reviewed in Avidor-Reiss and Fishman, 2019), an evolutionary process that drives sperm change due to post-ejaculatory competition between males (reviewed in Birkhead and Hunter, 1990; Humphries et al, 2008; Parker, 1970).…”
Section: Introductionmentioning
confidence: 99%